Anticancer activity of an antisense oligonucleotide targeting TRADD combined with proteasome inhibitors in chemoresistant hepatocellular carcinoma cells. (1st October 2013) - Witort, Ewa; Lulli, Matteo; Carloni, Vinicio; Capaccioli, Sergio
<x xml:space="preserve">Abstract</x> Chemoresistance is a major cause of mortality of patients with advanced and metastatic hepatocellular carcinoma (HCC), the fifth most common cancer in the world. We employed a molecular approach to inhibit cell proliferation and induce apoptosis in HepG2 cells, originated from human hepatocarcinoma. TRADD gene expression was knocked down by an antisense oligonucleotide (ASO TRADD), resulting in TRADD protein decrease by 60%, coinciding with increase of apoptotic cell death of up to 30%. Combination of the ASO TRADD with the cytotoxic drugs 5-fluorouracil or paclitaxel did not improve chemosensitivity of HepG2 cells, while the combined administration of the ASO TRADD with proteasome inhibitors MG132 or ALLN inhibited cell proliferation by 80% and 93%, respectively. Taken together, these findings reveal the importance to combine proteasome inhibitors with silencing of anti-apoptotic signalling components to target HCC cells effectively and provide useful data for developing potential treatments of HCC.